2014
DOI: 10.1186/1471-2164-15-984
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling shows gene regulation patterns in a flavonoid pathway in response to exogenous phenylalanine in Boesenbergia rotunda cell culture

Abstract: BackgroundPanduratin A extracted from Boesenbergia rotunda is a flavonoid reported to possess a range of medicinal indications which include anti-dengue, anti-HIV, anti-cancer, antioxidant and anti-inflammatory properties. Boesenbergia rotunda is a plant from the Zingiberaceae family commonly used as a food ingredient and traditional medicine in Southeast Asia and China. Reports on the health benefits of secondary metabolites extracted from Boesenbergia rotunda over the last few years has resulted in rising de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 82 publications
2
19
2
Order By: Relevance
“…3). Compared with previous B. rotunda transcriptome databases (Md-Mustafa et al, 2014), the average length and the N50 of unigenes in this study were much longer with nearly half of total unigenes were more than 1000bp in size. Therefore, all the data generated in this study indicated a relatively good overall integrity of the unigenes.…”
Section: Resultscontrasting
confidence: 78%
“…3). Compared with previous B. rotunda transcriptome databases (Md-Mustafa et al, 2014), the average length and the N50 of unigenes in this study were much longer with nearly half of total unigenes were more than 1000bp in size. Therefore, all the data generated in this study indicated a relatively good overall integrity of the unigenes.…”
Section: Resultscontrasting
confidence: 78%
“…For instance, the expression levels of 4CL gene in T10 cultures were up-regulated by twofold in comparison to C10 cultures, whereas T14 cultures were threefold higher than C14 cultures. In line with our previous study (Tan et al 2012;Md-Mustafa et al 2014), these findings indicated the promotive effect of phenylalanine in enhancing the selected flavonoid production.…”
Section: Effect Of Phenylalanine On the 4cl Gene Expressionsupporting
confidence: 91%
“…Hence, in this study, we analyzed the 4CL gene expression level after adding a precursor, phenylalanine, into B. rotunda cell which grown in full strength MS basal medium containing 1 mg/l NAA, 1 mg/l BA, and 3 % sucrose. Since our previous study showed that the amount of flavonoids produced was highest after 14 days of phenylalanine treatment before the cell growth decreased (Tan 2005;Tan et al 2012;Md-Mustafa et al 2014), the analysis of 4CL gene expression in this study was performed at 10 and 14 days of phenylalanine treatment.…”
Section: Effect Of Phenylalanine On the 4cl Gene Expressionmentioning
confidence: 99%
“…For medicinal plants, RNA-seq has been used to identify genes that are directly or indirectly involved in the biosynthetic pathways of target bioactive compounds22. Transcriptome analysis from only one plant organ or tissue does not provide a full transcript catalogue, even though it can serve numerous specific genetic and breeding objectives.…”
Section: Resultsmentioning
confidence: 99%
“…Primary metabolism is essential for plant growth, plant development and plant reproduction. In cell suspension cultures, primary metabolism is essential for plant cells to propagate in liquid media22.…”
Section: Resultsmentioning
confidence: 99%